Effect of entrance insulated inner absorber on EGATC thermal performance – experimental approach - Sulaiman, Nabila; Ihsan, Sany Izan; Abdul Majid, Zafri Azran; Syed Abu Bakar, Syed Noh (MMU Press, 2025)
This study presented the experimental results of using insulated inner absorbers to enhance the thermal performance of the Evacuated Glass Thermal-Absorber Tube Collector (EGATC). The inner absorber of EGATC was insulated with exterior thermal insulation paint. The length of the insulation varied at 20 cm, 30 cm, 40 cm, and 50 cm from the tip of the inner absorber. The thermal performance of the EGATC improved when the insulated inner absorber was utilized compared to instances without insulation. The optimal insulation length for enhancing EGATC’s thermal performance was found to be 35 cm from the projection. A follow-up experiment used the 35 cm insulation length to observe its thermal performance patterns. The 30 cm and 35 cm insulation lengths exhibited similar outlet temperatures during charging, confirming that 35 cm was the optimal length for insulating the inner absorber